(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes a mathematical model of the circulatory system for the cardiovascular system and provides a basic framework for the mathematical representation of cumulative medical parameters such as total vascular area about three-dimensional model of the flow of an incompressible viscous Newtonian fluid, blood volume, self-regulation, and effects on the upper and inner heart. In mathematical terms, linear dependencies, differential, integral and differential equations are used.